Targeting autophagy to treat HIV immune dysfunction - Wenli Mu; Heather Martin; Anjie Zhen (Autophagy Reports, 2023)
Chronic immune activation and inflammation are hallmarks of Human Immunodeficiency Virus-1 (HIV-1) pathogenesis. Therefore, approaches to safely reduce systematic inflammation are essential to improve immune responses and thus slow or prevent HIV progression. Autophagy is a cellular mechanism for the disposal of damaged organelles and elimination of intracellular pathogens. It is not only vital for energy homeostasis, but also plays a critical role in regulating immunity. However, how it regulates inflammation and antiviral T cell responses during HIV infection is unclear. Our study demonstrated that impairment of autophagy leads to spontaneous type I-Interferons (IFN-I) signaling, while autophagy induction reduces IFN-I signaling in macrophages. Importantly, we demonstrated that in vivo treatment of autophagy inducer rapamycin in chronically HIV infected humanized mice decreased chronic IFN-I signaling, improved exhausted anti-viral T cell function, and reduced viral loads. Taken together, our study supports the therapeutic potential of rapamycin and potentially other autophagy inducers in alleviating HIV-1 immunopathogenesis and improving anti-viral T cell responses.